Characterization of a Radish Nuclear Gene Expressed during Late Seed Maturation - Raynal, Monique (1989)
To study long-lived mRNAs stored in radish (Raphanus sativus) seed, we have selected clones from a dry seed cDNA library by differential screening. One of these clones, p8B6, whose mRNAs are abundant in the dry seed, was characterized. This clone hybridizes to an RNA class of approximately 600 nucleotides whose accumulation begins during the desiccation phase, reaches its maximum level in the dry seed, and is no longer detectable in 12 hour old seedlings. mRNAs hybrid-selected by p8B6 encode four polypeptides, but only two are compatible with the size class of RNAs detected by Northern analysis. Three of them have previously been identified as major `early germination' polypeptides, and their synthesis has been shown to be induced prematurely in immature embryos by a desiccation treatment. The protein deduced from the p8B6 nucleotide sequence is 9 kilodaltons in size, highly hydrophilic, rich in Gly and Glu, and contains no Cys, Trp, and lie. The amino acid sequence shares good homology with that of two recently described seed proteins: a cotton late embryogenesis abundant protein and the wheat early methionine-labeled protein. Southern blot analysis suggests that the p8B6 sequence belongs to a very small gene family. The exact function of the product encoded by p8B6 remains to be determined.